Neurosteroids and Seizure Activity - Miziak, Barbara; Chrościńska-Krawczyk, Magdalena; Czuczwar, Stanisław J. (Frontiers in Endocrinology, 2020)
Still circa 25% to 30% of patients with epilepsy cannot be efficiently controlled with available antiepileptic drugs so newer pharmacological treatment options have been continuously searched for. In this context, a group of endogenous or exogenous neurosteroids allosterically positively modulating GABA-A receptors may offer a promising approach. Among endogenous neurosteroids synthesized in the brain, allopregnanolone or allotetrahydrodeoxycorticosterone have been documented to exert anticonvulsant activity in a number of experimental models of seizures—pentylenetetrazol-, bicuculline- pilocarpine-, or 6 Hz-induced convulsions in rodents. Neurosteroids can also inhibit fully kindled seizures and some of them have been reported to counteract maximal electroshock-induced convulsions. An exogenous neurosteroid, alphaxalone, significantly elevated the threshold for maximal electroconvulsions in mice but it did not potentiate the anticonvulsive action of a number of conventional antiepileptic drugs against maximal electroshock-induced seizures. Androsterone not only elevated the threshold but significantly enhanced the protective action of carbamazepine, gabapentin and phenobarbital against maximal electroshock in mice, as well. Ganaxolone (a 3beta-methylated analog of allopregnanolone) needs special consideration for two reasons. First, it performed better than conventional antiepileptic drugs, diazepam or valproate, in suppressing convulsive and lethal effects of pentylenetetrazol in pentylenetetrazol-kindled mice. Second, ganaxolone has been evaluated in the randomized, double-blind, placebo-controlled phase 2 trial in patients with intractable partial seizures, taking maximally 3 antiepileptic drugs. The initial results indicate that add-on therapy with ganaxolone resulted in reduced seizure frequency with adverse effect being mainly mild to moderate. Possibly, ganaxolone may be also considered against catamenial seizures. Some positive effects of ganaxolone as an adjuvant were also observed in children with refractory seizures and its use may also prove efficient for the management of neonatal seizures associated with hypoxic injury. Neurosteroids positively modulating GABA-A receptor complex exert anticonvulsive activity in many experimental models of seizures. Their interactions with antiepileptic drugs seem ambiguous in mice. Initial clinical data indicate that ganaxolone may provide a better seizure control in patients with drug-resistant epilepsy.